An imaging-guided platform for synergistic photodynamic/photothermal/chemo-therapy with pH/temperature-responsive drug release. (September 2015) - Lv, Ruichan; Yang, Piaoping; He, Fei; Gai, Shili; Yang, Guixin; Dai, Yunlu; Hou, Zhiyao; Lin, Jun
Abstract: To integrate biological imaging and multimodal therapies into one platform for enhanced anti-cancer efficacy, we have designed a novel core/shell structured nano-theranostic by conjugating photosensitive Au25 (SR)18 – (SR refers to thiolate) clusters, pH/temperature-responsive polymer P(NIPAm-MAA), and anti-cancer drug (doxorubicin, DOX ) onto the surface of mesoporous silica coated core–shell up-conversion nanoparticles (UCNPs). It is found that the photodynamic therapy (PDT) derived from the generated reactive oxygen species and the photothermal therapy (PTT) arising from the photothermal effect can be simultaneously triggered by a single 980 nm near infrared (NIR) light. Furthermore, the thermal effect can also stimulate the pH/temperature sensitive polymer in the cancer sites, thus realizing the targeted and controllable DOX release. The combined PDT, PTT and pH/temperature responsive chemo-therapy can markedly improve the therapeutic efficacy, which has been confirmed by both in intro and in vivo assays. Moreover, the doped rare earths endow the platform with dual-modal up-conversion luminescent (UCL) and computer tomography (CT) imaging properties, thus achieving the target of imaging-guided synergistic therapy under by a single NIR light.